Pendidikan Konstitusi di Kelas IV SDN 067245 Kec Medan Selayang Kel Asam Kumbang - Desi Sri Kelengna Surbakti; Nadhilah Nazwa; Dini Syarafina; Anggita Uli Angel Gultom (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The aim of this research is to find out constitutional education in Class IV of SDN 067245, Medan Selayang District, Kel Asam Kumbang, and the process of implementing learning and what obstacles there are in the learning process at SDN 067245, Medan Selayang District, Kel Asam Kumbang. This research uses field research. The data sources used are primary data sources and secondary data sources from the Perdamean Village Office. Data were analyzed using qualitative descriptive methods. Teacher enthusiasm in seeing obstacles in the learning process. Increasing constitutional education in the implementation process.